Effects of a structured educational intervention on metabolic control of type-1 diabetes mellitus patients - Bernie Endyarni; Jose RL Batubara; I Boediman (Indonesian Pediatric Society Publishing House, 2016)
Background Children with type-1 diabetes face not only short- term complications but also long-term microvascular and macrovascular complications. Therefore, a continuing medical care and education to reach blood glucose near normal range is abso- lutely required. An addition of behavioral educational intervention to intensive diabetes management resulted in improved metabolic control and quality of life. Objective To determine the effects of a structured educational intervention to parents and patients with type-1 diabetes mellitus on their knowledge and patient metabolic control. Methods In this interventional study with pretest-posttest design at Department of Child Health, Medical School, University of Indo- nesia, a total of 21 patients with the age between 8 and 18 years and their parents were assigned to follow a structured educational program over period of 6 months. During the 6 intervention ses- sions, some procedures were applied: obtaining HbA1c at initial, 3 rd and 6 th month using HPLC procedure, classroom teaching pro- gram, small group discussions, role-playing and pre-posttests. Results The mean HbA1c level in the 21 children and adoles- cents at initial, 3 rd and 6 th month were 10.05% (SD 2.67%), 10.28% (SD 2.23%) and 10.01% (SD 2.67%), which showed no significant changes (P>0.05). After 6 educational sessions, the result showed significant changes in both parents' (P<0.05) and patients' knowl- edge (P<0.05). Patients' diabetes-related knowledge had a mod- erate correlation (r=-0.632; P=0.02) , but parents' diabetes-related knowledge had no significant correlation (r=-0.348; P=0.122) with patient mean HbA1c level. Conclusion A structured educational intervention used in this study is able to improve parents' and patients' diabetes-related knowl- edge significantly. Patients' diabetes-related knowledge had a sig- nificant correlation with metabolic control